IMPLEMENTASI PEMBELAJARAN KEWIRAUSAHAAN DALAM MENUMBUHKEMBANGKAN KARAKTER KEWIRAUSAHAAN PADA SISWA DI SMK NEGERI PERTANIAN TERPADU PROVINSI RIAU - Adhis Aulia; Suarman Suarman; Muhammad Nasir (Universitas Riau, 2020)
entrepreneurship learning on develop student entrepreneurship character in SMK Negeri Pertanian Terpadu Provinsi Riau. The sub focus research consist of 1).Learning models in the implementation of entrepreneurship learning on develop student entrepreneurship character, 2). The contribution of school citizens in the implementation of entrepreneurship learning on develop student entreprenurship character, and 3). The achievement of implementation entrepreneurship learning on develop student entrepreneurship character. Data was collected by interview, observation, and documentation. The results found that implementation of entrepreneurship learning on develop student entreprenurship character in SMK Negeri Pertanian Terpadu Provinsi Riau was implemented through learning models like discovery or inquiry learning, problem based learning, and project based learning. School citizens contribute to succeed the implementation of entrepreneurship learning by means of giving support for entrepreneurship learning, school creation and inovation, utilizing partner school as tutor, and build partnership for entrepreneurship learning. The school’s achievements in implementing entrepreneurship learning can be seen from the school’s achievements, relationships with partner schools, and school participation.